Effectiveness of a Web-Based Intervention to Increase Uptake of Maternal Vaccines. (4th October 2017) - O'Leary, Sean; Wagner, Nicole; Narwaney, Komal; Kraus, Courtney; Shoup, Jo Ann; Xu, Stanley; Omer, Saad; Gleason, Kathy; Daley, Matthew F; Glanz, Jason
Abstract: Background: Tetanus-diphtheria-acellular pertussis (Tdap) and influenza (flu) vaccines are recommended for all pregnant women in each pregnancy. However, vaccination uptake is suboptimal. Our objective was to test of the efficacy of an online vaccine and social media resource in increasing uptake of Tdap and flu vaccines. Methods: The RCT was conducted in an integrated health care system in Colorado from September 2013 to July 2016. Participants were pregnant women in the third trimester of pregnancy. Participants were randomly assigned to a website with vaccine information and interactive social media components (VSM), a website with vaccine information only (VI), or usual care (UC). To facilitate interaction on the VSM site, women were randomized 3:2:1 across the VSM:VI:UC arms. The interventions were designed and pilot tested using focus groups, individual interviews, surveys, and usability testing with vaccine-hesitant parents and pregnant women and included content on maternal and infant vaccination. Participants in the VSM and VI arms had access to the same base vaccine content. The VSM site also included a blog, discussion forum, chat room, and "Ask a Question" portal. After randomization, women in the VSM and VI arms were sent a website link. While they were encouraged to use the vaccine website, it was not required. Tdap and flu vaccination outcomes were analyzed separately. Women were included in each analysis if they had no record of vaccination for the relevant vaccine at enrollment and were >2 weeks from delivery. Results: For Tdap ( n = 172), there were no significant differences in uptake between study arms (VSM: 71%, VI: 69%, UC: 68%, P = .95). For flu ( n = 284), women in both the VSM and VI arms had higher rates of uptake compared with UC, although the intervention arms were not significantly different from each other (VSM: 57%, VI: 55%, UC: 38%, P = .09). Women receiving any intervention (VSM or VI) had significantly higher uptake of flu vaccine compared with UC (VSM/VI: 56%, UC: 38%, P = .03). Conclusion: Web-based vaccination information which is sent to pregnant women, with or without social media components, can positively influence maternal flu vaccine uptake. Because of the potential for scalability, the impact of robust vaccination information websites should be studied in other settings and with women in earlier stages of pregnancy. Disclosures: All authors: No reported disclosures.